Getting under the skin: Social isolation and biological markers in the National Health and Aging Trends Study. Issue 2 (26th October 2021) - Cudjoe, Thomas K. M.; Selvakumar, Sruthi; Chung, Shang‐En; Latkin, Carl A.; Roth, David L.; Thorpe, Roland J.; Boyd, Cynthia M.
Abstract: Background: Social isolation is a risk factor for morbidity and mortality comparable to well‐established risk factors including smoking, hypertension, and a sedentary lifestyle. The specific biological mechanisms that connect social isolation to morbidity and mortality remain unclear. Interleukin‐6 (IL‐6) and C‐reactive protein (CRP) are biological markers that are upregulated during inflammation and can have long‐term negative consequences for the health of individuals as they age. Methods: Utilizing Round 7 (2017) data from the National Health and Aging Trends Study (NHATS), we examine the relationship between social isolation and two biological markers: IL‐6 and high‐sensitivity CRP. This study included a nationally representative sample of 4648 Medicare beneficiaries 65 years and older who provided samples using dried blood spot (DBS) techniques. We defined social isolation utilizing a multi‐domained typology that considers living arrangement, core discussion network, religious attendance, and social participation. IL‐6 and CRP were obtained via DBS that were collected in Round 7 of the NHATS. We performed linear regression to examine the association between social isolation and biological markers IL‐6 and CRP. Results: After adjusting for age, gender, race/ethnicity, income, tobacco use, body mass index, and chronic conditions, we found that severe social isolation and social isolation were significantly associated with higher levels of IL‐6 and CRP values among older adults. Conclusions: Social isolation is associated with higher levels of biological markers (IL‐6 and CRP). Our findings inform the pathway between social isolation and morbidity and mortality among older adults. IL‐6 or CRP could be a proximal outcome measures for future clinical and social interventions that seek to alter the trajectory of social isolation and its associated health outcomes.